THE IMPLEMENTATION OF STORYTELLING A SHORT STORY TO IMPROVE MIDDLE SCHOOL SUNDANESE STUDENTS' SPEAKING SKILL - Hayati, Nuryani Nisa; Iqlimah, Siti; Aminah, Siti; Hikam, A Suny (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2024)
Speaking is one of the most important skills in learning English. However, a lot of students are good in reading, writing, and also listening but they are weak in speaking.  The purpose of this study was to implement storytelling a short story in students learning process to improve students speaking skill. While storytelling is usually associated with telling a long story, even so this study used short stories. This study used a qualitative method and to perform the research, two sessions were held. The first session was to find out students prior speaking skill and the second session was held after the research was conducted to find out the effectiveness of implementing storytelling a short story to improve students speaking skill. The researchers also used observation and interview to find out students challenge in speaking English. This study involved the second grade middle school of SMP IT Nurul Ittihad. The initial findings revealed that studentsâ€™ score in the second session was higher than in the first session. It can be concluded that there are improvements in students speaking skill.